The Analysis of The Effects of E-commerce Implementation and Operation in Technology and Non-Technology Industries in Taiwan: Sustainable Profitability Effects. - Hsu, Chieh (2017)
A rapid growth of electronic commerce (e-commerce) implementations is a global phenomenon in both technology and non-technology industries, these industries have not only developed their own brands in e-commerce, but have also devoted a lot of time and effort to online and offline integration to enhance their substantial competitive advantages. In this study, the qualitative case study research method is adopted to investigate and analyse four top international Taiwan enterprises, and two of them are technology corporations which manufacture 3C products, and the other two are non-technology firms which are automobile and bike manufacturers respectively.